THE ROLE OF VISUAL IMAGERY IN LITERARY STYLE: ANALYZING “THE GREAT GATSBY” BY F. SCOTT FITZGERALD - Ma’ripov Jalolxon Kamoliddin o‘g‘li; Sheraliyeva Shoira To‘lqin qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the pivotal role of visual imagery in shaping the literary style of F. Scott Fitzgerald’s “The Great Gatsby”. Through vivid descriptions and symbolic representations, Fitzgerald creates a rich tapestry that captures the decadence, disillusionment, and elusive nature of the American Dream. By examining key passages, this study highlights how visual imagery enhances thematic depth and emotional resonance. The analysis provides insights into the techniques Fitzgerald employs to immerse readers in the novel’s opulent yet morally ambiguous world.